O Serviço Ambulatorial Móvel de Urgência (SAMU) no contexto da reforma psiquiátrica: em análise a experiência de Aracaju/SE - Jardim, Katita Figueiredo de Souza Barreto (2008)
This research investigated professional practices from Mobile Urgency Care Service (Serviço Ambulatorial Móvel de Urgência - SAMU) at psychiatric cases of the city of Aracaju/SE, Brazil and its possible articulations to psychosocial services network. The regulation no. 2048 of 11/05/2002 from Ministry Health establishes National Urgency Policy and designates that psychiatric cases are SAMU's responsibility. Then, it is necessary to propose an analyze of psychiatric urgency service under anti-asylums social movements standpoint, mainly because this service is responsive in assisting a person in crises. Fieldwork was developed in two phases. First one was made with SAMU workers and the information were produced by recorded semi-structured interviews. Results of this first phase indicate that urgency psychiatric conception from SAMU workers is based on aggressiveness concept; delays at psychiatric cases support and low training in mental health care which means several difficulties to emergency service. Although, we noticed that SAMU use asylum procedures at psychiatric cases like ropes and odder instruments to contain people. The second step of our research was to attend meetings to build a new psychiatric urgencies protocol for SAMU to define practices to auxiliaries, vehicular conductors and medical support regulation. Therefore, open interviews were accomplished with some participators and follows-up to psychiatric case on board of SAMU's cars. Afterwards we discussed how the urgency paradigm, that influence the protocol draw and as consequence distort what we believe is the essentially function of this device, that is to give care support to persons in crises and produce articulation to psychosocial services network